Nutritional risk and a high NRS2002 score are closely related to disease progression and poor prognosis in patients with COVID-19 - Zhou, Yuanyuan; Chen, Yi; Zhang, Xinyi; Zhao, Bennan; Gao, Fengjiao; Yuan, Xiaoyan; Zhu, Yanfeng; Liu, Dafeng (Frontiers in Nutrition, 2023)
Background Organism can lead to excessive nutrient consumption in the infected state and increase nutritional risk, which is detrimental to the control of the infection and can further aggravate the disease. Objectives To investigate the impact of nutritional risk and the NRS2002 score on disease progression and prognosis in patients with COVID-19. Methods This was a retrospective cohort study including 1,228 COVID-19 patients, who were divided into a with-nutritional risk group (patients with NRS2002 score ≥ 3) and a without-nutritional risk group (patients with NRS2002 score < 3) according to the NRS2002 score at admission. The differences in clinical and outcome data between the two groups were compared, and the relationship between the NRS2002 score and the disease progression and prognosis of COVID-19 patients was assessed. Results Of 1,228 COVID-19 patients, including 44 critical illness patients and 1,184 non-critical illness patients, the rate of harboring nutritional risk was 7.90%. Compared with those in the without-nutritional risk group, patients in the with-nutritional risk group had a significantly longer coronavirus negative conversion time, significantly lower serum albumin (ALB), total serum protein (TP) and hemoglobin (HGB) at admission, discharge or 2 weeks, a significantly greater proportion with 3 or more comorbidities, and a significantly higher rate of critical illness and mortality (all p < 0.001). Multiple regression analysis showed that nutritional risk, NRS2002 score and ALB at admission were risk factors for disease severity. In addition, nutritional risk, NRS2002 score and TP at admission were risk factors for prognosis. The NRS2002 score showed the best utility for predicting critical illness and death in COVID-19 patients. Conclusion Nutritional risk and a high NRS2002 score are closely related to disease progression and poor prognosis in COVID-19 patients. For patients with NRS2002 score > 0.5, early intervention of malnutrition is needed to reduce the occurrence of critical disease. Additionally, for patients with NRS2002 score > 5.5, continuous nutritional support therapy is needs to reduce mortality and improve prognosis. Clinical Trial registration: [https://www.chictr.org.cn/historyversionpub.aspx?regno=ChiCTR2000034563], identifier [Chinese Clinical Trial Register ChiCTR2000034563].